2011
DOI: 10.1038/ja.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel RNase with antiproliferative activity from the mushroom Lactarius flavidulus

Abstract: A 14.6-kDa RNase, with a pH optimum of 5.5 and a temperature optimum of 70 1C, was isolated from dried fruiting bodies of the edible mushroom Lactarius flavidulus. The purification procedure involved, in succession, ion exchange chromatography on DEAE-cellulose, CM-cellulose and SP-Sepharose, and finally FPLC-gel filtration on Superdex 75. The RNase was adsorbed on all three ion exchangers. The ranking of its activity toward various polyhomoribonucleotides was poly(C) 4 poly(G) 4 poly(A) 4 poly(U). It suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Zhao et al (16) noted that Schizophyllum commune RNase had no effect on the proliferation of leukemia and lymphoma cells. Only a few mushroom RNases have been shown to inhibit the growth of leukemia cells (36,40,59,60). We found that the anti-proliferative activities of Hohenbuehelia serotina RNase toward L1210 cells are not as remarkable as those of Pleurotus sajor-caju RNase (40), but more effective than those of Hypsizigus marmoreus RNase (45).…”
Section: Inhibition Rates (%)mentioning
confidence: 85%
“…Zhao et al (16) noted that Schizophyllum commune RNase had no effect on the proliferation of leukemia and lymphoma cells. Only a few mushroom RNases have been shown to inhibit the growth of leukemia cells (36,40,59,60). We found that the anti-proliferative activities of Hohenbuehelia serotina RNase toward L1210 cells are not as remarkable as those of Pleurotus sajor-caju RNase (40), but more effective than those of Hypsizigus marmoreus RNase (45).…”
Section: Inhibition Rates (%)mentioning
confidence: 85%
“…The purified protein was stored in a buffer containing 10 mM Tris-HCl pH7.5, 50 mM NaCl, 4 mM DTT, and 40% glycerol. The ribonucleolytic activity of the purified EDN was assessed using the Kunitz assay that measures the release of nucleotides into the acid soluble fraction [58].…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] A 14.6 kDa RNase was purified from the fruit body of Lactarius flavidulus , which inhibited the proliferation of HepG2 cells and L1210 cells. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%